The Demands of Roles, Challenges, and Actions to Face the New Normal Era - Seger Handoyo (UM Purwokerto Press, 2021)
Employees, in all countries, are bearing a heavier burden in the COVID-19 pandemic situation. At least, there are three important issues that make the burden on employees, during the COVID-19 pandemic, heavier. First, is the conflict between the demands of work and family. Second, feelings of insecurity at work (job security). Third, related to the transmission of the COVID-19 virus. On the other hand, these employees are also faced with the challenges of new normal, so appropriate actions are needed when these employees return to work in the office.